Pengaruh Latihan Kelentukan Pergelangan Tangan Terhadap Kemampuan Pukulan Drive Dalam Permainan Bulutangkis Pada Siswa SMA Yadika Langowan - Teofilus Walangitan; Doortje Tamunu; Nofrie Sondakh (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
The formulation of the problem in this study is: Is there an effect of wrist flexibility exercises on the ability to drive strokes in badminton games for Yadika Langowan high school students? The research objectives were: to determine the effect of wrist flexibility exercises on the ability to drive strokes in badminton games for Yadika Langowan high school students. Research Hypothesis: There is an effect of wrist flexibility exercises on the ability to hit drive in badminton games for Yadika Langowan high school students. The research method used is the experimental method. The population of this study were all students of class XI SMA Yadika Langoawan and the sample consisted of 20 students who were taken randomly and then divided into 2 groups, namely group A as the experimental group with 10 students, and group B as the control group with 10 students. Data collection instrument: Drive Shot Test in Badminton Games. The research design used: Pre-test and post-test with randomized groups. Testing the hypothesis using statistical techniques with the t test. The results of calculations using the t-test statistic obtained the t observation value of tob = 4.079, while from the table the critical value of t with a significant level a = 0.05; n_1+n_2-2 obtained t table value as big as ttab = 2.101. This fact shows that the value of tob = 4.079 > ttab = 2.101, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.